Isolated subsegmental pulmonary embolism: Current therapeutic challenges - Yoo, Hugo H.B. [UNESP]; Marin, Flávia L. [UNESP] ("Medycyna Praktyczna" Spolka Jawna, 2020)
The advent of computed tomography pulmonary angiography allowed better visualization of peripheral vessels, thereby increasing rates of subsegmental pulmonary embolism (SSPE), but there are minimal changes in mortality. The true clinical significance of SSPE and isolated SSPE (ISSPE) remains unclear. Patients with small pulmonary embolism (PE) usually present with chest pain or no symptoms, frequently classified as having a low clinical probability of PE. Those with central embolism, on the other hand, present dyspnea as the most common symptom. It is possible that ISSPE could represent a subset of a more benign disease and be not clinically relevant among patients with PE. There is a therapeutic di- lemma in patients with small PE: should anticoagulation be used or not in all cases? As there are limited data to guide the appropriate management of ISSPE, this short review addresses the controversy over the therapeutic challenges in SSPE and ISSPE.
Keywords: Anticoagulation; Isolated subsegmental pulmonary embolism; Subsegmental pulmonary embolism; Treatment